Mozambique Tilapia Fish from Taliwang Lake as Bioindicator to Determine Lead Heavy Metal in 2022 - Era Meizaton Elfiza; Khairuddin Khairuddin; Kusmiyati Kusmiyati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the content of the heavy metal Lead (Pb) inmozambiqutilapia fish fromRawa Taliwag Lake and to find out whetermozambiqutilapia fish as a bioindicator originating from Rawa Taliwang Lake is suitable for consumption in accordance with The Indonesian Food and Drug Authority regulations Number 9 of 2022 concerning Requirements for Heavy Metal Contamination in Processed Foods. This research is a quantitative descriptive research. Sampling was carried out using purposive sampling method. The number of samples taken as many as 4 tails. The part taken is mozambiqutilapia fish meat which will then be analyzed using the Atomic Absorption Spectrophotometry (AAS) method. Sample analysis was carried out at the Analysis Laboratory of the Faculty of Mathematics and Natural Sciences, University of Mataram and the Environmental Laboratory Center for the Environment and Forestry Office of West Nusa Tenggara Province. This research took place from August 2022-March 2023. The results showed that the heavy metal content of Lead in the bodies of Lake fish from Rawa Taliwang Lake ranged from 0.197 mg/kg to 0.199 mg/kg so that an average of 0.197 mg/kg was obtained. Tilapia fish from Rawa Taliwang Lake is still below the threshold so it is still safe for consumption